Characterization of semi-extensive goat production systems in southern Spain - Castel, J M; Mena, Y; Delgado-Pertinez, M; Camunez, J; Basulto, J; Caravaca, F; Guzman-Guerrero, J L; Alcalde, M J (SMALL RUMINANT RESEARCH, 2003)
This study attempts to describe the semi-extensive goat fanning sector in Andalusia (south of Spain) and to establish characteristics. Eighty-nine goat farmers were surveyed in three areas of this region. The survey examined all aspects of the systems, from socio-economy to management. A multivariate analysis (multiple correspondence and cluster) was used to determine the different farm characteristics. Most of the goat farms studied are single-worker or family managed. The farmers lack training and are elderly, so that continuity of the activity is not assured, although newcomers are usually young. All the farms have some area in ownership, although the farms most specialized in dairy goat products are the smallest in both ownership and total area. The roads are generally in good condition, except on farms with little land, situated in areas of the sierra. Machine-milking installations, closely related to the presence of infrastructures and of goats with a dairy tendency, are generally lacking, (this aspect is improving day by day). Artificial nursing is less generalized than machine-milking. Farms specializing in milk production, whose main activity is dairy goat farming, have dairy specialized breed or crossbred (milk and meat) goats. Feeding depends largely on grazing, with little area being cultivated to produce feed for the goats. Little distinction is made for the production level. Olive or acorn tree branches (Quercus ilex spp.) are used as feedstuff, depending on the types of tree predominating in the area. Five farm types were established, the differences depending on 14 variables of socio-economic aspects, level of production, infrastructure and installations, and feeding. Generated information from this study entails an advance into knowledge of goat farming systems in the Mediterranean area (where little information is generated). The relevance of this study is important since Andalusia has 40% of goats in Spain that produce more than half of the total goat milk in the country, which points out the socio-economical importance for most depressed areas in the region. This work supposes previous steps for improving the semi-extensive goat farming sector. From a methodological point of view, the discussion on variable types and utility establishes farm type characteristics. (C) 2002 Elsevier Science B.V. All rights reserved.
Keywords: characterization methods; goat systems; semi-extensive farming; southern Spain